O-17 Searching for the holy grail? exercise and nutritional rehabilitation (ENeRgy) in patients with cancer. Issue Volume 8: Issue (2018)Supplement 2 (November 2018) - Hall, Charlie; Laird, Barry
Abstract : Background: Rehabilitation is advocated as an essential component of palliative care (Tiberini & Richardson, 2015) and is increasingly being adopted throughout various care settings. However, data on efficacy and key components of rehabilitation are lacking (Salakari, Surakka, Nurminen et al ., 2015). There is a persuasive argument that any rehabilitation programme should combine exercise and nutrition, which together may improve physical function and quality of life, but this needs to be assessed (Payne, Larkin, McIlfatrick et al ., 2013; Chasen, Bhargava, MacDonald, 2014).The ENeRgy trial will compare an Exercise and Nutrition based Rehabilitation programme with standard care, in patients with advanced cancer. The trial is funded by Marie Curie and the Chief Scientist Office. Aims: The primary aim of the ENeRgy trial is to assess the feasibility of an Exercise and Nutrition based Rehabilitation programme. Secondary aims will assess patient and partner-carer quality of life measures, functional and nutritional status, contamination of the control group and health economic impact. Methods: A single centre, randomised (1:1), unblinded feasibility trial is underway. Patients are randomised to receive an exercise and nutrition based rehabilitation programme (intervention) or standard care (control). Eligible patients meet the following criteria:>18 years; Karnofsky Performance Status>60; have incurable cancer; not currently undergoing anti-cancer treatment (bisphosphonates and hormone therapies are permitted). Results: The trial is recruiting until February 2019. Preliminary results are encouraging with 16% recruitment and 20% attrition rates. Patients are tolerating the individualised rehabilitation programme and positive feedback is emerging in terms of patient centred outcomes. Conclusions: The ENeRgy trial is a key step in defining, developing and assessing the feasibility of an outpatient, hospice based rehabilitation programme in this patient cohort. The results of this feasibility trial may pave the way for a wider, multi-centre trial to generate high quality evidence for rehabilitation in advanced cancer patients. This research has the potential to further guide the evolving arena of Rehabilitative Palliative Medicine.